Noise characterization of the operations of a manufacturing and marketing company of type 1 hydrolytic glass containers - Cano Arratea, Hermes Jilmer (2021)
The present investigation carried out a study on exposure to noise doses to workers in a company that manufactures, and markets hydrolytic glass containers type 1. The objective is to characterize the exposure profiles of the GES by comparing the results with the LMP. The study population is made up of all workers exposed to noise and the population of 103 and a sample of 45, the methodology used is that of the worst condition and according to the AIHA guidelines. The results were analyzed according to two indicators, maximum value for samples smaller than 6 and in case of higher evaluations it was analyzed under the UCL, obtaining as results 9 groups of GES, of which 89% present a level of exposure without hearing protection greater than the LMP.